(untitled) (TAMADDUN NURI JURNALI, 2025)
This article highlights the spelling and pronunciation of terms in the Uzbek language as used in the Microsoft Windows operating system. Additionally, the article examines the usage and validity of both adapted and translated terms that appear among Windows terminology.